CSR in Universities: A Case Study on Internal Stakeholder Perception of University Social Responsibility - Ismail, Dr. Zeenat; Ismail, Dr. Zeenat; Shujaat, Neshmia (Advances in Social Sciences Research Journal, 2019)
Research in CSR has generated a clear understanding on the role of and expectations from sustainable corporations. However, little attention has been directed towards non-corporate institutions such as universities, whose purpose and responsibilities are too ambiguous for any evaluations on them. The aim of this study is to contribute to the sparse literature on University Social Responsibility. This aim is achieved by investigating internal stakeholders’ perception of their university’s social responsibility initiatives to learn the initiatives that most impact their satisfaction with the institution. The first stakeholder group included 229 undergraduate students and were categorized on basis of their gender, degree program and semester. The second stakeholder group included 75 employees, both administrative and teaching faculty and were categorized on gender, age, tenure, and education level. Results showed that students, especially from Business programs and employees were most satisfied when they perceived their university providing quality education, strong industry linkages and equal opportunities to all stakeholders. Specifically, for employees, satisfaction levels and USR perceptions grew positively as their university tenure increased. However, after a tenure of 10 years, there was a slight decrease in employee satisfaction and USR perceptions. Both stakeholder groups gave little importance to their university’s initiatives on research and innovation, implicating that future research should probe into the cross-cultural relevance of research work at universities.